Implementasi Model Pembelajan Inovatif Sebagai Penguatan Kompetensi Siswa Abad 21 Mata Pelajaran Pendidikan Pancasila - Fitria Lutfiana, Rose; Syahri, M; Nurhadianto, Nurhadianto; Dianti, Puspa (University of Muhammadiyah Malang, 2024)
This research aims to analyze the implementation of innovative learning models as strengthening 21st century student competencies. The research approach used is qualitative with a descriptive type. This research was conducted in 2023. Data collection techniques used interviews, observation and documentation studies with interview guide, observation guide and documentation guide instruments. The data analysis technique consists of four stages, namely data collection, data reduction, data presentation and drawing conclusions. Based on the results of research on strengthening 21st century student competencies, namely: (1) Critical thinking, as many as 0 students (0%) were in the very poor category, 2 students (11%) were in the poor category, 5 students (27.7%) were in the fair category, 7 students (38.8%) in the good category and 4 students (22.2%) in the very good category; (2) Student collaboration was 0 students (0%) in the very poor category, 0 students (0%) in the poor category, 3 students (16.6%) in the sufficient category, 8 students (44.4%) %) in the good category and 7 students (41.1%) in the very good category; (3) Student creativity was 0 students (0%) in the very poor category, 0 students (0%) in the poor category, 2 students (11.1%) in the sufficient category, 7 students (38.8%) %) in the good category and 9 students (50%) in the very good category; (4) Student communication was 0 students (0%) in the very poor category, 1 student (5.5%) in the poor category, 2 students (11.1%) in the sufficient category, 7 students (38 .8%) in the good category and 8 students (44.4%) in the very good category.